Inhalation of Water Vapor and Eucautious Oil to Improve the Clearance of the Airways of Pulmonary Tuberculosis Patients - Nining Trikusumawati; Shindi Hapsari (Jurnal EduHealth, 2026)
Pulmonary tuberculosis remains a major health problem and is often accompanied by ineffective airway clearance due to excessive sputum production. This case study aimed to describe the effectiveness of warm steam inhalation combined with eucalyptus oil in improving airway clearance among patients with pulmonary tuberculosis. The study involved three patients treated in the Mawar Ward of Dr. Adhyatma, MPH Regional General Hospital using a nursing process approach based on SDKI, SLKI, and SIKI standards. Nursing interventions included warm steam inhalation with eucalyptus oil, semi-Fowler positioning, effective coughing techniques, and adequate fluid intake. The results showed consistent clinical improvement in all patients, indicated by increased oxygen saturation, decreased respiratory rate, reduced dyspnea, and more effective sputum expectoration. These findings suggest that warm steam inhalation combined with eucalyptus oil is an effective non-pharmacological nursing intervention to support airway clearance in patients with pulmonary tuberculosis.